Sylvia Pankhurst, the First World War and the struggle for democracy - Katherine Connelly (Revue Française de Civilisation Britannique)
The rallying of much of the feminist movement to support for the government, and even to enthusiasm for the war in 1914 is well-known. This article looks at a leader of a section of the suffragettes which followed a very different path. Sylvia Pankhurst broke with her patriotic mother and sister to work among working women in the East of London, using dynamic and original forms of activism to defend working women’s interests and encourage left wing consciousness.